SCREENING OF MULTI BIOACTIVE METABOLITES PRODUCING MICROORGANISMFROM GARDEN SOIL OF DR. M. G. R EDUCATIONAL AND RESEARCH INSTITUTE, CHENNAI - SENTHILRAJR; S., GEJALAKSHMI; M., THARUNKUMAR; A., SANTHOSH; V., LOKESH; B. A., TANISHA (International Journal of Current Pharmaceutical Research, 2020)
Objective: Screening of industrial important bioactive metabolites of Antibiotics, hydrolytic enzymes producing microorganism from garden soil of Dr. M. G. R Educational and Research Institute, Chennai. Methods: Desired ten soil samples taken and were serially diluted. Crowded plate method used for antibiotic-producing microorganism and Starch agar medium and gelatin medium tests were performed for hydrolytic enzymes (Amylase and Gelatinase). Results: Among the tested soil samples, antibiotic producing microorganisms were not found, but has hydrolytic enzymes amylase and gelatinase. Thus screened soil samples biochemically identified as Bacillus species. Conclusion: This study concludes that, the collected sample, produced Antibiotic negative result and it’s possess other industrial important hydrolytic enzymes. Thus Screening of more bioactive metabolites producing ability from a single isolate, will be more useful for effective screening.